Korean Painting from modern to contemporary, 1945-1980s - Cho, Ŭn-jŏng (Contemporary Korean Arts Series, 2015)
This book is for those who are curious about the modern history of Korean art, especially in the fields of the painting. It shows various developing stages and historical contexts of Korean art since the liberation. The readers will take an interest to the ceaseless struggles of Korean painters and understand the sided causes of actions behind the various conflicts between the generations, schools, and tendencies.